Temporary Employment, Permanent Stigma? Perceptions of Temporary Agency Workers Across Low- and High-Skilled Jobs - Pia Cardone; Markus Tümpel; Christian M. Huber (Qualitative Sociology Review, 2021)
Research on temporary agency work emphasizes that temporary agency workers (TAWs), particularly those in low-skilled jobs associated with precariousness and low social prestige, are likely to be exposed to poor treatment, as well as stigmatization. On the contrary, stigmatization of TAWs in high-skilled jobs has not been treated in much detail in previous studies. Literature provides an incomplete picture of stigmatization within the broader field of temporary employment regarding the focus on low-skilled jobs. Hence, the present qualitative study is based on data from interviews of a heterogeneous sample of TAWs employed in low- and high-skilled jobs in Germany. By using and modifying Boyce and colleagues’ (2007) model of stigmatization, the study shows that stigmatizing treatment towards TAWs occurs across all skill levels, although the intensity and form of those experiences, as well as coping strategies, differ. Thereby, this study contributes to a more differentiated and skill level-specific understanding of how TAWs perceive and cope with stigmatization linked to their employment status. It also provides an important opportunity to advance Boyce and colleagues’ (2007) complex model of TAW stigmatization with empirical underpinnings.